The Issue of Women in Science: Exploring the Gender Gap in Egypt's Scientific Research Productivity. - Saleh, Yomna (AUC Knowledge Fountain, 2021)
Research productivity and impact are highly valued in the scientific field. It is regarded as a significant determinant of career advancement, financial support, academic recognition, and prominent personal position. Unfortunately, this is an area that has demonstrated a long history of gender disparity. This quantitative study aims to validate and identify gender gaps concerning women’s research productivity to help assess effectiveness of interventions and policies aiming to improve female participation and representation in scientific research. Although, gender gap in scientific publications is a global phenomenon, but this should not mask potential variations at both the national and regional levels. Hence this study is contributing to the thin literature under this topic on the Arab region, focusing our analysis on Egyptian researchers. The study lies at the intersection between bibliometrics and econometrics using classic bibliometric indicators as the main variables under testing. Original data was constructed and harmonized for the purpose of this study, extracted from Scopus Elsevier, the largest citation and abstract database in the world. The study applies descriptive statistics, regression models, and secondary research to examine characteristics of our sample, test co- relations, and learn about potential women positive deviants. The study demonstrates a gender gap in scientific research productivity and impact disfavoring Egyptian women scientists and in line with majority of global literature assumptions. It argues the importance of number of remedial policies and strategies on institutional, national, and global levels.